New species of small, bathypelagic calanoid copepods from the Arctic Ocean: Brodskius arcticus sp. nov. (Tharybidae) and three new species of Pertsovius gen. nov. (Discoidae) - Andronov, Vladimir N.; Kosobokova, Ksenia N. (Zootaxa, 2011)
A new calanoid copepod species, Brodskius arcticus sp. nov. (family Tharybidae Sars, 1902), and three new species of a new genus Pertsovius gen. nov. (family Discoidae Gordejeva, 1975) are described from deep waters of the Arctic Canada Basin. The female of Brodskius arcticus differs from five of the other six known species of this genus in the absence of rostral filaments, the lack of which it shares with B. abyssalis Markhaseva & Schulz, 2007. This new species differs from B. abyssalis in having two very short outer proximal spines at the distal segment of the fifth swimming legs (P5). The length of these spines is less than half the width of the segment, whereas in B. abyssalis they are longer than the width of the segment. The new genus Pertsovius is created here for a group of seven species within the family Discoidae which have one-segmented endopods of Р 2-Р4. In contrast, the other genera of this family have three-segmented endopods of Р 2-Р4. The three new species of Pertsovius differ from each other in the appearance of the genital field, and in the number of outer border spines on the distal exopodal segment of P2. In Pertsovius tridentatus sp. nov. this segment bears three external spines on both left and right P2. The left Р 2 of P. heterodentatus sp. nov. has three spines, while the right Р 2 bears two spines only. The distal segments of both left and right Р 2 of P. serratus sp. nov. have two external spines, but the proximal part of the external margin on the left Р 2 bears three relatively large denticles. The distal exopodal segments of Р 2 of the other four species here transferred to the genus Pertsovius are smooth with no external spines or denticles, but each bears two outer border spines.